Comparative end-of-life communication and support in hospitalised decedents before and during the COVID-19 pandemic: a retrospective regional cohort study in Ottawa, Canada - Shirley H Bush; Monisha Kabir; Peter Lawlor; James Downar; Brandi Vanderspank-Wright; Sarina Isenberg; Peter Tanuseputro; Akshai Iyengar; Claire Dyason; Julie Lapenskie; Colleen Webber; Henrique Parsons; et al. (BMJ Open)
Objective To compare end-of-life in-person family presence, patient–family communication and healthcare team–family communication encounters in hospitalised decedents before and during the COVID-19 pandemic.Design In a regional multicentre retrospective cohort study, electronic health record data were abstracted for a prepandemic group (pre-COVID) and two intrapandemic (March–August 2020, wave 1) groups, one COVID-19 free (COVID-ve) and one with COVID-19 infection (COVID+ve). Pre-COVID and COVID-ve groups were matched 2:1 (age, sex and care service) with the COVID+ve group.Setting One quaternary and two tertiary adult, acute care hospitals in Ottawa, Canada.Participants Decedents (n=425): COVID+ve (n=85), COVID-ve (n=170) and pre-COVID (n=170).Main outcome measures End-of-life (last 48 hours) in-person family presence and virtual (video) patient–family communication, and end-of-life (last 5 days) virtual team–family communication encounter occurrences were examined using logistic regression with ORs and 95% CIs. End-of-life (last 5 days) rates of in-person and telephone team–family communication encounters were examined using mixed-effects negative binomial models with incidence rate ratios (IRRs) and 95% CIs.Results End-of-life in-person family presence decreased progressively across pre-COVID (90.6%), COVID-ve (79.4%) and COVID+ve (47.1%) groups: adjusted ORs=0.38 (0.2–0.73) and 0.09 (0.04–0.17) for COVID-ve and COVID+ve groups, respectively. COVID-ve and COVID+ve groups had reduced in-person but increased telephone team–family communication encounters: IRRs=0.76 (0.64–0.9) and 0.61 (0.47–0.79) for in-person, and IRRs=2.6 (2.1–3.3) and 4.8 (3.7–6.1) for telephone communications, respectively. Virtual team–family communication encounters occurred in 17/85 (20%) and 10/170 (5.9%) of the COVID+ve and COVID-ve groups, respectively: adjusted OR=3.68 (1.51–8.95).Conclusions In hospitalised COVID-19 pandemic wave 1 decedents, in-person family presence and in-person team–family communication encounters decreased at end of life, particularly in the COVID+ve group; virtual modalities were adopted for communication, and telephone use increased in team–family communication encounters. The implications of these communication changes for the patient, family and healthcare team warrant further study.